PENEGAKAN HUKUM TERHADAP PEDAGANG PAKAIAN BEKAS IMPOR DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Used clothing is an object or item used by humans to cover their bodies but has been worn by people, used clothing is called flea goods. Imported used clothing is prohibited from being traded because this used clothing has the potential to endanger human health so it is not safe to be used and used by the community and does not have the Indonesian National Standard (SNI). However, in reality every regulation contained in Law Number 7 of 2014 concerning trade and Regulation of the Minister of Trade of the Republic of Indonesia Number 51 / M-DAG / PER / 7/2015 concerning the prohibition of importing used clothing is not implemented and enforced by enforcement officers the law against import used clothing traders in the city of Pekanbaru, Even used clothing sales are sometimes conducted overtly so that the writer is interested in researching about Law Enforcement Against Imported Used Clothing Merchants in Pekanbaru City.The purpose of this thesis, namely; First, to find out law enforcement against imported used clothing traders in the city of Pekanbaru, Second, to find out the inhibiting factors in law enforcement against imported used clothing traders in Pekanbaru city.The type of legal research used by the writer is sociological law research. This research was conducted in Pekanbaru City. Sociological legal research uses primary data and secondary data, while population and sample are parties related to the problem under study, namely the Head of Trade of the Department of Industry and Trade of Pekanbaru, Kanit II of the City of Pekanbaru Criminal Investigation Unit and used clothing traders. Data collection techniques in this study with literature review and interviews.From the results of this study, the author concludes that the Law Enforcement of Imported Used Clothing Merchants in Pekanbaru City has so far only been carried out socialization on imported used clothing traders by the Pekanbaru City Industry and Trade Office without carrying out any follow-up on the used clothing traders. Factors that hinder the law enforcement against imported secondhand clothing traders in Pekanbaru city are the absence of Civil Servant Investigators, the lack of awareness and concern of the community towards the law, the import of used clothing trade is entrenched, and the geographical location of the city of Pekanbaru.Keywords: Law Enforcement-Trade-Used Clothing